2014
DOI: 10.3390/ijerph111111438
|View full text |Cite
|
Sign up to set email alerts
|

Intrahippocampal Infusion of Crotamine Isolated from Crotalus durissus terrificus Alters Plasma and Brain Biochemical Parameters

Abstract: Crotamine is one of the main constituents of the venom of the South American rattlesnake Crotalus durissus terrificus. Here we sought to investigate the inflammatory and toxicological effects induced by the intrahippocampal administration of crotamine isolated from Crotalus whole venom. Adult rats received an intrahippocampal infusion of crotamine or vehicle and were euthanized 24 h or 21 days after infusion. Plasma and brain tissue were collected for biochemical analysis. Complete blood count, creatinine, ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Moreover, due to its cell-penetrating capacity and site-specific interactions, crotamine has been studied as a drug-mediating peptide and as a model for the discovery of new antitumor molecules [10,17,19,21,22,23]. However, data on crotamine safety for local and systemic application in biological models are scarce [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, due to its cell-penetrating capacity and site-specific interactions, crotamine has been studied as a drug-mediating peptide and as a model for the discovery of new antitumor molecules [10,17,19,21,22,23]. However, data on crotamine safety for local and systemic application in biological models are scarce [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Using an intra-hippocampal application route, Gonçalves et al [25] observed that crotamine altered the oxidative parameters in the serum of animals after 21 days. These results suggest that crotamine has the ability to induce an imbalance in the systemic redox system for a long time, regardless of the route of administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation